ANALISIS PROSES PEMBELAJARAN MEDIA GAMBAR KARTU TERHADAP KEMAMPUAN BERBICARA PADA ANAK USIA 5-6 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL SAPEN YOGYAKARTA - Utia Virli Susanti; Ruliana Fajriati; Desy Susanti (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
The speaking ability of children aged 5-6 years can be given good stimulation by using picture cards as media. The media can attract the interest and attention of the child, demanding that the presentation be clearer and make it easier for the child to understand what the educator is conveying. This research is qualitative, the subjects in this research are school principals, teachers, and children, and the data collection method uses observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and conclusion. Furthermore, to determine the validity test of the data using a triangulation technique using a single source of multiple research techniques. The results of the study show that (1) the learning process with card picture media can be seen from the teacher's planning using procedures related to the themes being taught, media use equipment, group systems, variations in picture media, and RPPH. (2) the learning design with card image media can be seen from the opening activity, which explains related to training habituation, the core activity contains media explanations, and color variations. And the closing activity explains the repetition of the learning process. (3) The results of the use of card image media can be seen from observations such as observing student learning activities, then a thorough note that records various student learning activities, and then a weekly report book (connection book). which recaps the child's activities for one week.